2016
DOI: 10.1002/1873-3468.12471
|View full text |Cite
|
Sign up to set email alerts
|

Trip12 is an E3 ubiquitin ligase for USP7/HAUSP involved in the DNA damage response

Abstract: The deubiquitinating enzyme, USP7/HAUSP (herpesvirus-associated ubiquitin-specific protease), is a key regulator of the tumor suppressor p53 and plays a major role in regulating genome stability. Here, we report that the protein stability of USP7 is regulated by the ubiquitin-proteasome pathway. We identified the thyroid hormone receptor interactor 12 (Trip12) as a ubiquitin E3 ligase for USP7. We also found that Trip12 affects USP7-mediated stabilization of p53 and the checkpoint proteins 53BP1 and Chk1. Knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 41 publications
3
27
0
Order By: Relevance
“…Further proteomic studies of the RNF169-DYRK1A complex in the cells before and after DNA damage will help to identify such factor. Of note, our analysis of DYRK1A interactome reported here detected the interaction with USP7, a ubiquitin-specific protease that has been recently shown to bind directly to RNF169 and increase the stability of 53BP1, RNF169 and RNF168 [40,[65][66][67]. Although disruption of the DYRK1A phosphorylation sites in RNF169 did not influence its interaction with USP7, the role of USP7 in the DYRK1A-RNF 169 mediated regulation of 53BP1 should be further investigated.…”
Section: Discussionmentioning
confidence: 68%
“…Further proteomic studies of the RNF169-DYRK1A complex in the cells before and after DNA damage will help to identify such factor. Of note, our analysis of DYRK1A interactome reported here detected the interaction with USP7, a ubiquitin-specific protease that has been recently shown to bind directly to RNF169 and increase the stability of 53BP1, RNF169 and RNF168 [40,[65][66][67]. Although disruption of the DYRK1A phosphorylation sites in RNF169 did not influence its interaction with USP7, the role of USP7 in the DYRK1A-RNF 169 mediated regulation of 53BP1 should be further investigated.…”
Section: Discussionmentioning
confidence: 68%
“…68 On another hand, overexpression of TRIP12 (R SILAC = 1.62) produces inhibition of USP7, which is an ubiquitin specific processing protease whose depletion induce cell cycle arrest at the S phase. 69 The inhibition of a big part of the proteins found altered in the study also has effects on cell proliferation. Different studies carried out in hepatocarcinoma cells such as Huh-7 or HepG2 (cells employed in our work) have shown that an inhibition of SHMT2 (R SILAC = 2.26) or RFC3 (R SILAC = 1.91), is translated into an inhibition of cell proliferation and tumorigenicity 70 by stabilization of p21, p53 and p57, and the inhibition of the cyclin A.…”
Section: Quantitative Proteomicsmentioning
confidence: 90%
“…Unsurprisingly, overexpression of USP7 and TRIP12 has been found to be associated with poor prognosis in cancers with aberrant expression of p14 ARF , such as hepatocellular carcinoma (HCC) [131]. Interestingly, USP7 itself is also targeted by TRIP12 for proteasomal degradation, indicating that they are mutual substrates for each other [132]. Thus, USP7 increases the stability of TRIP12, whereas the TRIP12 does the opposite for USP7.…”
Section: Substrate Recruitment and Catalytic Activity Regulationmentioning
confidence: 99%